Barriers to Physical Activity in Spanish Children and Adolescents: Sex and Educational Stage Differences - Delfa-De-La-Morena, José Manuel; Bores-García, Daniel; Solera-Alfonso, Adrián; Romero-Parra, Nuria (Frontiers in Psychology, 2022)
According to worrisome childhood obesity levels worldwide, this work aimed to address the lacking knowledge about barriers to meet physical activity (PA) requirements and international guidelines in Spanish children and adolescents considering the entire educational pathway. The Short Form of the International PA Questionnaire and the Scale of Perceived Barriers were administered to primary, secondary and college education students (13491 boys and 13238 girls, 9 – 19 yrs). Two-way ANOVA was performed to analyze barriers to PA according to sex and educational stage with physical status as covariate. Higher disliking and time barriers were reported by females (1.5±1.2 and 3.2±1.5 points) in comparison to males (1.2±1.0 and 2.8±1.4), while primary students showed lower disliking and time (1.2±1.0 and 2.8±1.5) and higher safety (3.1±1.8) constraints in comparison to secondary (1.4±1.1, 3.1±1.4 and 2.8±1.7) and college (1.5±1.2, 3.2±1.5 and 2.8±1.6) (p<0.05 for all comparisons). College females showed higher disliking (1.7±1.2) and time (3.5±1.4) barriers than secondary females (1.5±1.2 and 3.3±1.4) (p<0.05). Spanish female students rated barriers to PA higher and showed lower PA levels than their male counterparts. From primary education onwards higher barriers and lower PA were observed. The main barriers reported were the lack of time and dislike of PA.